UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK BUAH DAN KULIT PISANG JARUM (Musa acuminata var. Jarum (AA Group)) - Fensia Analda Souhoka; Yeanchon H Dulanlebit; Ester M. C Tomasoa (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
This study aimed to determine phytochemical tests and antioxidant activity of fruit and peel extract of pisang jarum. Sample was extracted with 80% of ethanol, methanol, and acetone using reflux method. The result showed that pisang jarum extract contains phenols, flavonoids, and terpenoids, whereas peel extract contains phenols, flavonoids, terpenoids, alkaloids, and saponins. The total phenol content (TPC) of pisang jarum is 0.0250-0.0316 mg PE/g extract and peel is 0,1756-0,2679 mg PE/g extract. The total flavonoid content (TFC) of pisang jarum is 0.8412-1.4466 mg QE/g extract and peel is 3.2128-5.1073 mg QE/g extract. The antioxidant activity of extract were analyze by DPPH free radical scavenging activity. The antioxidant activities (IC50) of pisang jarum is 1092.92-3871.24 ppm and peel is 310.08-558.07 ppm, so it is classified as a weak antioxidant